Vascular risk factors and depression in later life: A systematic review and meta-analysis - Valkanova, V; Ebmeier, K (2013)
Reports of the association between cardiovascular risk factors and depression in later life are inconsistent; to establish the nature of their association seems important for prevention and treatment of late-life depression. We searched MEDLINE, EMBASE, and PsycINFO for relevant cohort or case control studies over the last 22 years; 1097 were retrieved; 26 met inclusion criteria. Separate meta-analyses were performed for Risk Factor Composite Scores (RFCS) combining different subsets of risk factors, Framingham Stroke Risk Score, and single factors. We found a positive association (odds ratio [OR]: 1.49; 95% confidence interval [CI]: 1.27-1.75) between RFCS and late-life depression. There was no association between Framingham Stroke Risk Score (OR: 1.25; 95% CI:.99-1.57), hypertension (OR: 1.14; 95% CI:.94-1.40), or dyslipidemia (OR: 1.08; 95% CI:.91-1.28) and late-life depression. The association with smoking was weak (OR: 1.35; 95% CI: 1.00-1.81), whereas positive associations were found with diabetes (OR: 1.51; 95% CI: 1.30-1.76), cardiovascular disease (OR: 1.76; 95% CI: 1.52-2.04), and stroke (OR: 2.11; 95% CI: 1.61-2.77). Moderate to high heterogeneity was found in the results for RFCS, smoking, hypertension, dyslipidemia, and stroke, whereas publication bias was detected for RFCS and diabetes. We therefore found convincing evidence of a strong relationship between key diseases and depression (cardiovascular disease, diabetes, and stroke) and between composite vascular risk and depression but not between some vascular risk factors (hypertension, smoking, dyslipidemia) and depression. More evidence is needed to be accumulated from large longitudinal epidemiological studies, particularly if complemented by neuroimaging. © 2013 Society of Biological Psychiatry.